In the Time of COVID-19: Love and Transformations in the Family - Cersosimo, Giuseppina; Marra, Patrizia (Italian Sociological Review, 2020)
In recent months, COVID-19 has distorted our everyday life in unexpected and violent ways, irreversibly devastating our apparently strong world structures. Although each country has tried to cope with the crisis, the repercussions on health, economy, social and family life, have quickly emerged around the world. The pandemic has redefined the criteria for health and well being as much as the virus itself. Moved by this unprecedented emergency, the family suffers the effects of the virus in a mirror like way quite different from the effect on the individuals in that space, whose relationships - out of equilibrium - fall apart when hit by the classic tension-accommodation dichotomy (Simmel, 1895). This tension is generated by the fear of death and disease, keeping pace with the growth of the pandemia, a common realization byway of an uncertain future; as well as by the financial strains that weigh on an already precarious personal and family economy, as well as by the expression of feelings that change our language and relationship to each other, proposing caution and circumspection. Within the home, time and personal space are necessarily subject to new forms of management, sharing, and redefinition. We have used a qualitative methodology of narrated communication using semi-structured interviews and in-depth interviews. Our research illustrates ways in which understanding the impact of the pandemic on our families and the new vulnerabilities that derive from it, activate mechanisms to contain the tensions associated with them and the new needs that gradually emerge.